PEMBAGIAN WARIS PADA MASYARAKAT JAWA DITINJAU DARI HUKUM ISLAM DAN DAMPAKNYA - Anggita Vela (AS-SALAM, 2015)
Although Islamic law and Javanese customary law basically havesimilarities, especially in the type and status of inheritance, there aredifferences in the use and distribution of inheritance, the heirs, andthe children. In this paper will explain about how the implementationof the division of inheritance in Java society.In terms of time of Javanese community heritage there is a system thatis not in line with Islamic inheritance law. Islamic law is the processof transferring property from the heir to the heirs after the deceasedis declared dead. And what happens to the Javanese community is theheir to distribute his inheritance before the heir died. Meanwhile, interms of heirs as well as its part, the pattern of division of Javaneseheritage that is with the system of peace or kinship.